Pengembangan pangan lokal untuk mendukung peningkatan ketahanan pangan dan pariwisata Wakatobi: Pelatihan pembuatan “Kasoami Instan” - Abdul Madiki; Tamrin Tamrin; La Ode Nafiu; La Ode Alifariki; Musram Abadi (DEDIKASI, 2019)
Training on Making "Instant Kasoami". The problems formulated were (1) the community of cassava producers in Wakatobi did not yet have the knowledge and skills to make instant cassettes which were required, which were attractive, long-lasting, and preserving product nutrition. The purpose of this training is to develop local processed food products in the framework of supporting food security and tourism in Wakatobi. The objectives of the training are to: (1) Improve the knowledge and skills of the community of kasoami makers in making attractive instant kasoami, long shelf life, and maintaining product nutrition; (2) Making local cassava food processed products as a support for food security and tourism in Wakatobi. Training participants are women who daily make and / or sell kasoami. Total participants were 20 people, consisting of 10 people from Wangi-Wangi District and 10 people from South Wangi-Wangi District. The training is carried out with adult education methods that focus on direct practice of the activity material. Some characteristics of instant Soami training results are as follows: in the processing process, steamed in a pressure cooker; the size of instant soami is smaller than that of citizens of soami; Soami instant packed aluminum foil; Instant Soami can be stored for up to 10 days without changes in structure, texture, and taste. Using the vacuum method, instant soami can be produced which can be stored for more than a month.